1996
DOI: 10.1021/jp9537825
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Perchlorate:  Ab Initio Study of the Structural and Spectral Changes Associated with Ion Pairing

Abstract: The anion ClO 4 -and the ion pair of Li + ClO 4 -have been studied by ab initio quantum chemical methods. Optimized geometries for monodentate, bidentate, and tridentate structures have been determined up to the MP2/6-311+G* level of theory. Vibrational frequencies were determined for the ClO 4 -anion and the Li + ClO 4 -ion pair up to the HF/6-311+G* level of theory. Comparisons are made with experimental Raman spectra of electrolyte solutions. At the highest level of theory, the bidentate structure was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 19 publications
7
48
0
Order By: Relevance
“…The maxima for Li-O x and Li -Cl agree also with the results of Ref. [9], where the preferred arrangement of the lithium and perchlorate ions was a bidentate configuration with the Li-O distance about 1.9 Å , whence the LiCl distance should be about 2.4 Å . These distances Table 1 The contributions to the stabilization energy for lithium ions in the four configurations shown in Fig.…”
Section: Simulated Structuressupporting
confidence: 89%
See 1 more Smart Citation
“…The maxima for Li-O x and Li -Cl agree also with the results of Ref. [9], where the preferred arrangement of the lithium and perchlorate ions was a bidentate configuration with the Li-O distance about 1.9 Å , whence the LiCl distance should be about 2.4 Å . These distances Table 1 The contributions to the stabilization energy for lithium ions in the four configurations shown in Fig.…”
Section: Simulated Structuressupporting
confidence: 89%
“…The force field parameters were mostly as described in Ref. [8], but some modifications were required to keep the perchlorate anions in a tetrahedral geometry with the Cl -O bond length about 1.45 Å , consistent with the results of a study [9] of ion pairing in LiClO 4 . One approach would be to freeze the ions in the requested geometry as ''rigid bodies'', but in Cerius 2 this would be possible only for the energy minimization, because the dynamics simulation does not support rigid bodies.…”
Section: Simulated Structuresmentioning
confidence: 84%
“…It is well known in the literature that DFT (including B3 LYP/6‐31+G(d)) and lower levels of ab initio theory usually underestimate the frequency of symmetric stretching vibrations of highly symmetric species. For example, the theoretical frequency of the totally symmetric stretching vibration of the perchlorate anion (ClO 4 − ) is always lower than that experimentally observed 59. The same situation occurs for the totally symmetric stretching vibration of the tetrahedral chloroaluminate AlCl 4 − , for which theory underestimates the experimental data by 4.5 % 60.…”
Section: Resultsmentioning
confidence: 74%
“…SCF MO calculations for LiClO 4 by Klassen et al 28 confirmed the low-wavenumber shift of the 1 band for a bidentate configuration and showed that the electron density for the Li C -O bond in a monodentate is higher than in a tridentate structure. SCF MO calculations for LiClO 4 by Klassen et al 28 confirmed the low-wavenumber shift of the 1 band for a bidentate configuration and showed that the electron density for the Li C -O bond in a monodentate is higher than in a tridentate structure.…”
Section: Solutions Inmentioning
confidence: 87%